2020
DOI: 10.1007/s40264-020-01014-2
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Guidelines: Best Practices for Detection, Assessment and Management of Suspected Acute Drug-Induced Liver Injury During Clinical Trials in Adults with Chronic Viral Hepatitis and Adults with Cirrhosis Secondary to Hepatitis B, C and Nonalcoholic Steatohepatitis

Abstract: With the widespread development of new drugs to treat chronic liver diseases (CLDs), including viral hepatitis and nonalcoholic steatohepatitis (NASH), more patients are entering trials with abnormal baseline liver tests and with advanced liver injury, including cirrhosis. The current regulatory guidelines addressing the monitoring, diagnosis, and management of suspected drug-induced liver injury (DILI) during clinical trials primarily address individuals entering with normal baseline liver tests. Using the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 180 publications
(254 reference statements)
0
24
0
Order By: Relevance
“…The serum levels of AST and ALT, two key enzymes in the biological process, are routinely assessed for liver function prior to clinical treatment ( 20 ). The De Ritis ratio (AST/ALT) was initially thought to be a valuable diagnostic marker for the etiology of hepatitis (e.g., acute viral hepatitis) ( 8 ), while the association between an elevated De Ritis ratio and poor prognosis of various cancers has been subsequently found ( 21 24 ), including HCC ( 25 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The serum levels of AST and ALT, two key enzymes in the biological process, are routinely assessed for liver function prior to clinical treatment ( 20 ). The De Ritis ratio (AST/ALT) was initially thought to be a valuable diagnostic marker for the etiology of hepatitis (e.g., acute viral hepatitis) ( 8 ), while the association between an elevated De Ritis ratio and poor prognosis of various cancers has been subsequently found ( 21 24 ), including HCC ( 25 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid accumulation in liver parenchymal cells and subsequent toxicity can result from excessive inflammation and liver damage [ 21 ]. Moreover, HFD can cause an increase in free fatty acids (FFAs) in serum, with the continuous accumulation of FFAs causing liver damage, increasing cell-membrane permeability and the release of ALT and AST into the circulation, where they are frequently used as important markers of the degree of liver damage [ 22 ]. In the present study, we observed increases in serum ALT and AST levels accompanied by increases in TC, TG, and LDL levels and a decrease in HDL content in NAFLD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Such a systematic understanding would allow candidate interventional molecules of all types to be made with low adverse event liability from the beginning, the current practice of making many molecules with unpredictable liabilities, most of which fail in later stages of testing. Several industry‐based and public‐private partnerships have made early progress in predictive toxicology via massive data generation and sharing efforts, including the International Consortium for Innovation and Quality in Pharmaceutical Development (IQ) biopharmaceutical collaborative drug safety program (e.g., Treem et al 29 ); the BioCelerate subsidiary of the pharmaceutical company collaborative TransCelerate BioPharma Inc.; the Critical Path Institute's Predictive Safety Testing Consortium (e.g., Schomaker et al 30 ), and the Innovative Medicines Initiative eTox 31 and TransQST programs. The Toxicology in the 21st Century program, a collaborative effort among NCATS, the National Toxicology Program, the Environmental Protection Agency, and the US Food and Drug Administration (FDA) has also made promising advances in this area, 32 but much more needs to be achieved before accurate and reliable prediction of common and idiosyncratic toxicities is possible.…”
Section: A Research Agenda For the Next Decade Of Translational Sciencementioning
confidence: 99%